Analisis Kualitas Jaringan Internet di Gedung Guntur: Studi Kasus pada Tenant Call Center PT Jasnita Telekomindo - Thoriq Zibaltar; Desi Ramayanti (JSAI (Journal Scientific and Applied Informatics), 2023)
This research aims to measure the quality of the internet network in Gedung Guntur, which is owned by PT Jasnita Telekomindo and houses a call center tenant. The staff of the call center have complained about the slow internet connection when inputting reports in the CRM system and making phone calls to customers. Therefore, this research is conducted to measure network parameters, such as throughput, delay, and packet loss, by implementing Quality of Service (QoS) on voice and CRM data. The measurement is performed using Axence Net Tools 5 software. The results of the testing show that the bandwidth parameter has a value of 3.086 Kbps, throughput has a value of 1.918 Kbps, delay has a value of 1 ms, and packet loss has a value of 0%. If these test results are compared with the TIPHON standard, the parameters achieve an index of 4, indicating excellent network quality. This research provides a clearer understanding of the quality of the internet network in Gedung Guntur and indicates that the network meets the TIPHON standard. The results of this research can be used as a basis for identifying necessary improvement or enhancement measures to improve the service quality in Gedung Guntur.